Association between physical activity and health-related quality of life among adults in China: the moderating role of age - Hao, Hongying; Yuan, Yemin; Li, Jie; Zhao, Dan; Li, Peilong; Sun, Jingjie; Zhou, Chengchao (Frontiers in Public Health, 2024)
Objective The aim of the study was to examine the association between physical activity (PA) and health-related quality of life (HRQOL) among adults and explore the role of age in the association between PA and HRQOL in Shandong, China. Methods We investigated the relationship between PA and HRQOL and examined the moderated role of age in this association among adults with different age groups and physical activity levels. Data were obtained from the sixth China National Health Services Survey conducted in Shandong province in 2018. The multi-stage-stratified cluster random sampling method was used to selected respondents, with individuals aged 18 and above included in the present study. The tool of assessing HRQOL was the three-level EuroQol Five Dimensions Questionnaire (EQ-5D-3L). Results The study found PA was significantly related to HRQOL (P < 0.05). The interaction analysis indicated that the relationship between PA and HRQOL was significantly different across young, middle-aged, and older adults (P < 0.05). Older adults with the sufficient PA (coefficient = 0.090, 95%CI: [0.081, 0.100]) and active PA (coefficient = 0.057, 95%CI: [0.043, 0.072]) had significantly higher HRQOL compared with young and middle-aged groups. Conclusion PA was positively associated with HRQOL among the adults. Age played a moderate role between the association between PA and HRQOL. Guidelines for PA should be specifically tailored to adults of different age groups in order to enhance their HRQoL.